MEMOTONG EKSTRIMISME DARI HULU: DERADIKALISASI PEMAHAMAN AGAMA DI SEKOLAH MENENGAH ATAS KOTA METRO - Wildani Hefni; Imam Mustofa (Balai Penelitian dan Pengembangan Agama Jakarta, 2020)
Abstract Institution-grown extremism is among the most urgent challenges confronting societies today. Attempts to understand extremism often treat this development as a form of the political education system. This study explores by starting actual experiences of radicalization and discover a great diversity of experiences from the leaders of Senior High Schools. This study explores the role of education institutions in Senior High Schools in Metro in confronting the radicalization of religious outlooks among students by analyzing their activities. The results of this study showed that radicalization is not something done to people, but something produced by active participants. From this phenomenon, the leaders of educational institutions in Senior High School conducted a practical guide to the de-radicalization of religious outlooks by various programs. In addition, organizations by religious affiliation have influenced religious formation among students both of religious organizations affiliated to Nadhlatul Ulama and Muhammadiyah. Keywords: De-radicalization, religious outlooks, Senior High Schools